The EU's Shifting Borders : Theoretical Approaches and Policy Implications in the New Neighbourhood. - Bachmann, Klaus (Routledge/Garnet Series., 2011)
The EU's internal borders have become mostly invisible. Today, external borders are at the centre of controversy about an alleged 'fortress Europe'. Using different theoretical and methodological perspectives this book examines the challenges facing the EU's external borders, including Neighborhood Policy, migration issues and the diffusion of norms and values to other countries. Divided into two parts, the book first presents different theoretical approaches and empirical studies of the EU's external borders, mobility and security issues. It is an invaluable guide to border research within a.